Effect of genotypes on reaction time, refractory period, semen index and liquid stored semen quality of breeding bulls in Bangladesh - Sharad Chowdhury; Mohammad Mahbubul; Md. Ahsan Habib; Md. Younus Ali; Auvijit Saha Apu (Fundamental and Applied Agriculture, 2023)
The present study was conducted with the aim to reveal the effect of genotypes on reaction time, refractory period, semen index and liquid stored (at 4oC) semen quality of breeding bulls in Bangladesh. Semen was collected twice a week from Holstein Friesian, Sahiwal and Brahman breeding bulls. Reaction time and refractory period were examined for the breeding bulls. Semen volume, sperm concentration and total spermatozoa/ejaculate were measured immediately after collection. It was revealed that genotype had a significant (P [Fundam Appl Agric 2023; 8(3.000): 555-566]